Pengembangan Sektor Pariwisata Sentani: Penilaian Strategis SWOT Objek Wisata Bukit Bhulem Mokho dan Bhanjibey - Kekri, Boy Piter Nizu; Mende, Fabiola Valensia (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2026)
The purpose of this study is: 1) To determine the strengths, weaknesses, opportunities, and threats in the development of Bhulem Mokho and Bhanjibey Hill tourism, 2) To develop an effective development strategy to maximize the tourism potential of Bhulem Mokho and Bhanjibey Hill, 3) To see the activeness of the local community in the development of the two hills. This study uses qualitative data obtained through direct interaction with the research object. The analysis method used in this study is SWOT data analysis, namely Strengths, Weaknesses, Opportunities, and Threats. The results of the study show that: 1) The SWOT Cartesian quadrant of the Bhulem Mokho Hill Tourism Object in Ifar Besar Village, in Quadrant 1 shows an aggressive growth strategy pattern, the strategy implemented in quadrant 1 is to support an aggressive growth policy, through the development of the Bhulem Mokho Hill Tourism Object which is profitable, has strengths and opportunities. 2) The SWOT analysis of the Bhanjibey Hill tourist attraction in Hobong Village, in Quadrant II, shows a strategic pattern indicating a diversification policy. The strategy implemented in Quadrant II is to support diversification policies, the development of the Bhanjibey Hill tourist attraction, indicating a situation where the Bhanjibey Hill tourist attraction has internal weaknesses, but there are external opportunities that can be utilized to overcome these weaknesses. 3) The local communities of Ifar Besar and Hobong villages have implemented the development of the Bhulem Mokho and Bhanjibey Hill tourist attractions related to several development aspects according to the local economy and Creative Economy Development Regulation No. 24/2022 of 2022, including: location, workforce, security, and social capital. Although still minimal, the commitment and initiative of the local community, community leaders, land rights owners, and village government officials have become the seeds for the realization of the Bhulem Mokho and Bhanjibey Hill tourist attraction. Keywords: Tourism Sector, Assessment, Strategic SWOT